PANTANG LARANG SUKU HUTAN KECAMATAN TEBINGTINGGI - Nur Aini; Abdul Jalil; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study discusses the forms of abstinence in public bans Tebingtinggi tribal forest districts. Bans abstinence is viewed from the perspective of the life cycle. Include life cycle : birthm children, adolescents, adults, dies. This study used a qualitative approach and descriptive method that aims to describe and explain the problem to be studied abstinence prohibited. Data source of this study allowed the ban abstinence from interviews with tribal communities Tebingtinggi forest districts. Data obtained using. Teknik collecting data, then the data is classified in the form of data recording and data observation judged to be the conclution based on the analisys of the data, allowed 5 staged in the life cycle of them: (1) birth (2) children (3) adolescents (4) adults (5) died.Keywords: Abstinence banned